Contributions of Romance Languages to Current Linguistic Theory - Arteaga, Deborah L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume presents novel analyses of morphosyntax and phonology by well-known scholars in their respective fields. The book offers chapters on a range of Romance languages and dialects, including Canadian French, Standard French, Modern French, Sardinian, Sicilian, and Spanish. Other chapters focus on diachronic topics on French and Italian. The volume will be of interest to researchers looking for current research in linguistics on the Romance languages. It will also serve as a reference volume or supplemental reading for graduate students and advanced undergraduate students in linguistics.
Introduction; Julia Herschensohn -- Part I Romance Syntax -- Classifier Phrase as Host for Stage-level Spanish Adnominal Participial Adjectives; Karen Zagona and Heles Contreras -- The Syntax of Mirative Focus Fronting: Evidence from French; J.-Marc Authier and Liliane Haegeman -- Further Implications of French Devoir and Falloir for Theories of Control and Modality; Lisa A. Reed -- Part II Language Variation in Romance -- Theoretical and Practical Arguments for a Language Feature: Evidence From Language Mixing; Barbara E. Bullock & Almeida Jacqueline Toribio -- On the Reduction of /ʒ/ in a Minority North American Variety of French; Randall Gess; Why Lenition Interactions are Typically Counter-feeding; Haike Jacobs -- The French Jespersen's Cycle and Negative Concord; Marie Labelle -- Part III Diachronic Romance Studies -- The Variable Position of Initial Subordinate clauses in Old French: arguments Against a semantic account; Bryan Donaldson -- Obviation and Old French Subjunctive Clauses; Deborah Arteaga -- On the varying fortunes of darla and darlo in Italian; Cinzia Russi -- Conclusion; Julia Herschensohn.
Keywords: Grammar, Comparative and general -- Syntax; Grammar, Comparative and general -- Phonology; Grammar, Comparative and general -- Morphology; Romance languages; Syntax; Phonology and Phonetics; Morphology; Romance Languages